Efficient Method of Choosing Potential Parents and Hybrids: Line ? Tester Analysis of Spring Wheat (Triticum aestivum L.) Cultivars: Combining Ability of Wheat Genotypes (Biological Sciences - PJSIR, 2011)
The study was conducted to estimate the general combining ability (GCA) and specific combining ability (SCA) of wheat genotypes crossed in a line ´ tester fashion. The mean squares due to F1 hybrids, female lines, male testers/pollinators and lines ´ tester interaction were significant for majority of thecharacters studied. The significance of GCA and SCA variances thus suggested that both additive and non- additive genes were controlling majority of the characters, yet additive genes were more prominent because variances due to GCA by and large were higher than due to SCA. Among the three female lines evaluated, Khirman displayed maximum positive GCA effects for spike length (0.08) and seeds/spike (0.67), while other female lines which showed maximum positive GCA effects were Mehran for plant height (3.05), number of tillers/plant (1.00), spikelets/spike (1.92) and seed index (3.42) and Kiran for seeds/spike (0.67) and yield/plant (1.86). From the male testers, TD-1 exhibited greater GCA effects for number of tillers/plant (2.96), spikelets/spike (0.25), seed index (0.61) and yield/plant (2.22), whereas, Marvi displayed highest positive GCA effects for plant height (2.88), spike length (0.37) and seeds/spike (6.41). The specific combining ability estimates indicated, if hybrid crop development is feasible then, crosses Mehran ´ TD-1 for spike length; Kiran ´ TD-1 for plant height and seeds/spike and Khirman ´ Marvi for number of tillers/plant, spikelets/spike, seed index and yield/plant may be the hybrids of choice.